(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
For millennia, experts have paid close attention to a tiny evergreen shrub known as a lemon because it has such a magical and mystical significance. It is not only utilized as a food source, but it also has therapeutic and nutritional value. According to nutritionists, eating instead of taking medication improves the odds of long-term healing or reduces the risks of adverse effects. Lemon plants are known for their thorny branches and white blooms with purple borders. Citrus lemon has anti-cancer properties, as well as the ability to prevent kidney stones. Bring a fever to a halt and restore ph balance. Citral, limonene, terpineol, geranyl acetate, and linalyl are phytochemicals found throughout the entire plant. Similarly, if people start their day with lemon, it reduces fat and cleanses the digestive systems; if people apply it to their skin, people will have the most lustrous or acne-free skin ever. If people drink it with honey, it will assist to alleviate sore throats, constipation, or a variety of other ailments. In summary, it is beneficial to people of all ages and genders, from tiny bee stings to big kidney stones.